2016
DOI: 10.1007/s11239-016-1441-5
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding risk associated with eptifibatide (Integrilin) bridging in thoracic surgery patients

Abstract: Objective Antiplatelet use for treatment of coronary artery disease (CAD) is common amongst thoracic surgery patients. Perioperative management of antiplatelet agents requires balancing the opposing risks of myocardial ischemia and excessive bleeding. Perioperative bridging with short-acting intravenous antiplatelet agents has shown promise in preventing myocardial ischemia, but may increase bleeding. We sought to determine whether perioperative bridging with eptifibatide increased bleeding associated with tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Among them, 6 studies [ 11 , 12 , 14 , 16 18 ] included 215 patients that used tirofiban for bridging therapy. Four studies [ 13 , 15 , 19 , 20 ] had 167 patients that used eptifibatide for bridging therapy.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, 6 studies [ 11 , 12 , 14 , 16 18 ] included 215 patients that used tirofiban for bridging therapy. Four studies [ 13 , 15 , 19 , 20 ] had 167 patients that used eptifibatide for bridging therapy.…”
Section: Resultsmentioning
confidence: 99%
“…Reports of the use of abciximab and tirofiban prior to surgical procedures have shown higher rates of intraoperative bleeding with these agents, although recent reports found that a dose of 2 µg/kg/min of eptifibatide (reduced in impaired renal function) infused after stent implantation as a bridge to surgery did not cause excessive bleeding events or stent thrombosis. [17][18][19][20][21] Advantages of cangrelor over eptifibatide for this purpose may include more rapid drug elimination, allowing a shorter preprocedural washout period, and potentially lower drug costs with the dosing regimen of cangrelor described within this experience. 1,22 Table 3 provides cost comparisons with cangrelor at doses of 0.5 and 0.75 µg/kg/min with that of eptifibatide 2 µg/kg/min, based on a patient weight of 80 kg and median duration of cangrelor therapy of 5 days using average wholesale prices.…”
Section: Discussionmentioning
confidence: 99%
“…6 A small, retrospective, single-center study analyzed the use of eptifibatide as a bridging agent in patients with recent or high-risk PCI on DAPT awaiting thoracic surgery. 7 The outcomes assessed the number of units of blood transfused during the periprocedural period, MACE, and postoperative complications (cardiovascular complications, reintubations, reoperations, renal failure, or confusion). Periprocedural bridging with eptifibatide was not associated with an increased risk of bleeding defined by the number of blood transfusion when compared with patients who did not undergo bridging.…”
Section: Introductionmentioning
confidence: 99%